Pemberdayaan Masyarakat Desa Renon Melalui Pembuatan Hand Sanitizer Organik di Tengah Pandemi Covid-19 - Maria Yunita Apriyati (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2021)
Antiseptics are substances that can inhibit the growth and development of pathogenic microorganisms such as viruses, bacteria, parasites, and fungi. aloe vera is a functional plant that is widely cultivated in Indonesia. Research shows aloe vera contains saponins, flavonoids, polyphenols, and tannins which are antiseptic. By utilizing aloe vera in Renon village, especially on Jalan Tukad Badung 18, Bali, South Denpasar, it can help local communities to maintain or develop the family economy during this pandemic. By introducing innovative and creative antiseptic products or hand sanitizers and the addition of aloe vera and lime juice, this product can make this product a way of dealing with viruses and bacteria in the midst of the Covid-19 virus in Indonesia so that people can maintain a healthy lifestyle.One of the goals is to make innovative products that are good for health and open employment opportunities for students and the general public. Hand sanitizers made of aloe vera are effective at killing germs and are also very efficient and economical during the Covid-19 pandemic.